2007
DOI: 10.1105/tpc.106.049676
|View full text |Cite
|
Sign up to set email alerts
|

The Two AGPase Subunits Evolve at Different Rates in Angiosperms, yet They Are Equally Sensitive to Activity-Altering Amino Acid Changes When Expressed in Bacteria

Abstract: The rate of protein evolution is generally thought to reflect, at least in part, the proportion of amino acids within the protein that are needed for proper function. In the case of ADP-glucose pyrophosphorylase (AGPase), this premise led to the hypothesis that, because the AGPase small subunit is more conserved compared with the large subunit, a higher proportion of the amino acids of the small subunit are required for enzyme activity compared with the large subunit. Evolutionary analysis indicates that the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 84 publications
(111 reference statements)
5
72
1
Order By: Relevance
“…These observations confirm the idea that different AGPases in a given tissue have distinct regulatory properties depending on the specific LSs present (Ballicora et al 2004). Plant AGPase LS genes could be categorized into five major groups according to their sequences and expression patterns (Georgelis et al 2007). Group 1 comprised genes expressed in monocot and eudicot leaf tissue.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These observations confirm the idea that different AGPases in a given tissue have distinct regulatory properties depending on the specific LSs present (Ballicora et al 2004). Plant AGPase LS genes could be categorized into five major groups according to their sequences and expression patterns (Georgelis et al 2007). Group 1 comprised genes expressed in monocot and eudicot leaf tissue.…”
Section: Discussionsupporting
confidence: 65%
“…These data are in accord with the idea that tissue identity has influenced the rate of evolution of both SSs and LSs of AGPase. Expression in multiple tissues would then compound the various selection pressures exerted by the different tissues (Georgelis et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Georgelis et al (2007) showed that, whereas this difference is due to greater evolutionary constraints on the small subunit, the two subunits are equally predisposed to activity-altering mutations when expressed in one tissue with one complementary subunit. The difference in the rate of sequence divergence apparently is caused by the fact that plants generally have fewer small subunit genes than large subunit genes.…”
mentioning
confidence: 99%
“…While bacterial AGPases are homotetramers, plant and unicellular green algae AGPases are composed of two identical small subunits and two identical large subunits (for review, see Georgelis et al, 2007). Prokaryotic and eukaryotic AGPases have different quaternary structures and regulatory properties (Ballicora et al, 2003), yet their overall kinetic mechanisms appear to be similar (Paule and Preiss, 1971;Kleczkowski et al, 1993).…”
mentioning
confidence: 99%